Artificial Vision Model Based on Deep Learning to Prevent Thefts in Real Estate (LACCEI, 2024)
Artificial intelligence has become an increasingly present concept today. Terms such as Machine Learning or Deep Learning are frequently used in the development of technological projects. These can generate an impact in the solution of various social problems that, unfortunately, are experienced every day in many countries worldwide. One of them is citizen security, a problem that has been a setback, especially in less developed countries. Citizen insecurity has expanded so much that, over the years, large numbers of thefts have even been observed in people's real estate properties. However, as mentioned above, it is currently possible to develop technological models that can support the arrest of these criminal acts. Artificial vision is one of the many scientific disciplines of artificial intelligence, and with it it is possible to carry out a security project with the ability to detect faces and identify them as users known as possible suspects.